Improving college students’ depression during an acute pandemic disease with the KEEP application - Mengyao, Chao; Tengku Kamalden, Tengku Fadilah; Omar Der, Roxana Dev; Binti Harun, Maizatul Mardiana; Xiaoxiao, Liu (Australian International Academic Centre PTY LTD, 2024)
Background: During the Covid-19 epidemic, the number of downloads of sports apps surged, with people using sports apps to exercise and share social activities. Objective: This study aimed to explore the impact of college students using Keep APP to exercise on their mental health during the COVID-19 lockdown. Methods: This study utilized a longitudinal research methodology to conduct a 6-week intervention experiment with college students using the KEEP application based on the intervention criteria of the study. The psychological status of the university students before and after the experiment was evaluated through the Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS). On the basis of satisfying the normal distribution, the was used for data analysis. Results: A total of 60 college students participated in this study (22 boys and 38 girls). Among them, 46 people (76.7%) were infected with COVID-19. After a 6-week exercise intervention using Keep APP, through paired-sample t-tests, significant differences were observed in SDS scores before and after the experiment (t = 10.33, p = 0.051). The mean difference was 5.82, with a 95% confidence interval of [6.436, 9.197], indicating a moderate effect on depressive emotions in the experimental group. Similarly, SAS scores also showed significant differences before and after the experiment (t = 4.889, p = 0.005). The mean difference was 2.18, with a 95% confidence interval of [1.88, 4.486], demonstrating a moderate to large effect.There was no statistically significant effect of choice of exercise modality and frequency of exercise per week on scores in this study (P>0.05). Additionally, the duration of exercise shows a significant effect on SAS scores (P =0.027). Conclusion: This study verified the impact of using Keep APP on the mental health of college students during the COVID-19 outbreak, and confirmed that the application can help improve students with mental health problems. These findings provide help in dealing with people’s mental health problems during sudden infectious diseases. Similarly, it also provides valuable insights for further research on software applications.